Experimental and theoretical perspectives of the Noyori-Ikariya asymmetric transfer hydrogenation of imines - Václavík, Jiří; Sot, Petr; Pecháček, Jan; Vilhanová, Beáta; Matuška, Ondřej; Kuzma, Marek; Kačer, Petr (Molecules (Basel, Switzerland), 2014)
The asymmetric transfer hydrogenation (ATH) of imines catalyzed by the Noyori-Ikariya [RuCl(η6-arene)(N-arylsulfonyl-DPEN)] (DPEN=1,2-diphenylethylene-1,2-diamine) half-sandwich complexes is a research topic that is still being intensively developed. This article focuses on selected aspects of this catalytic system. First, a great deal of attention is devoted to the N-arylsulfonyl moiety of the catalysts in terms of its interaction with protonated imines (substrates) and amines (components of the hydrogen-donor mixture). The second part is oriented toward the role of the η6-coordinated arene. The final part concerns the imine substrate structural modifications and their importance in connection with ATH. Throughout the text, the summary of known findings is complemented with newly-presented ones, which have been approached both experimentally and computationally.
Keywords: Hydrogenation; Molecular Structure; Ruthenium; Catalysis; Stereoisomerism; molekulární struktura; hydrogenace; iminy; Imines; katalýza; stereoizomerie; ruthenium